1999
DOI: 10.1128/jb.181.17.5341-5349.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cold Shock Response of Bacillus subtilis : Isoleucine-Dependent Switch in the Fatty Acid Branching Pattern for Membrane Adaptation to Low Temperatures

Abstract: Bacillus subtilis has developed sophisticated mechanisms to withstand fluctuations in temperature. Membrane fatty acids are the major determinants for a sufficiently fluid membrane state to ensure the membrane’s function at all temperatures. The fatty acid profile of B. subtilis is characterized by a high content of branched fatty acids irrespective of the growth medium. Here, we report on the importance of isoleucine for B. subtilis to survive cold shock from 37 to 15°C. Cold shock experiments with strain JH6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(99 citation statements)
references
References 47 publications
8
90
1
Order By: Relevance
“…The lipidic tail of surfactin also exhibits heterogeneity. The length and isomery of the lipopeptide's FA chain are known to have an impact on the lipopeptide properties, particularly for the antifungal activities of the mycosubtilin anteisoC 17 [11,12] and for the surfactant property of the surfactin [13]. This property is enhanced in the order straight (n) > iso > anteiso.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The lipidic tail of surfactin also exhibits heterogeneity. The length and isomery of the lipopeptide's FA chain are known to have an impact on the lipopeptide properties, particularly for the antifungal activities of the mycosubtilin anteisoC 17 [11,12] and for the surfactant property of the surfactin [13]. This property is enhanced in the order straight (n) > iso > anteiso.…”
Section: Research Articlementioning
confidence: 99%
“…B. subtilis contains high percentage of branched chain FA in comparison to straight FA irrespective of medium conditions [17,18]. The β-OH fatty acid of the surfactin can be iso, anteiso or nC 13 ; iso or nC 14 , iso, anteiso or nC 15 and iso or nC 16 [2].…”
Section: Research Articlementioning
confidence: 99%
“…The above changes led to an overall decrease in the anteiso/iso ratio of fatty acids during growth on ONB and PHB as compared to the succinate-grown cells. The ratio of anteiso/iso fatty acids plays an important role in the maintenance of the membrane fluidity, as reported in the case of Bacillus subtilis, where this ratio was increased during its growth at low temperature (Klein et al, 1999). It was reported that the iso and anteiso forms of C15 : 0 fatty acid have different transition temperatures, 51.7 1C and 23.0 1C, respectively, and this difference influences the fluidity of the membrane (Kaneda, 1991).…”
Section: Resultsmentioning
confidence: 88%
“…The second strategy of membrane adaptation is the introduction of de novo synthesized branched-chain fatty acids into the membrane to reduce the interactions between the fatty acid residues. These changes in the constitution of the fatty acids have already been well studied (Kaneda, 1991;Aguilar et al, 1998;Klein et al, 1999;Weber et al, 2001). a-keto acids are used as precursors for the de novo synthesis of branched-chain fatty acids in B. subtilis MR168 (Kaneda, 1977(Kaneda, , 1991.…”
Section: Introductionmentioning
confidence: 99%
“…After a short time of adaptation, a new balance of protein synthesis in the cell at 15 1C is established. Problems arising after a cold shock include a slow down in initiation of translation due to stabilized secondary structures of mRNA (Broeze et al, 1978;Hall et al, 1982;Wulff et al, 1984;Graumann et al, 1997) and an increased rigidification of the membrane, which results in cell lysis (Grau & de Mendoza, 1993;Klein et al, 1999;Aguilar et al, 2001).…”
Section: Introductionmentioning
confidence: 99%